EDUCATIVE BOARD GAME DESIGN AS AN ANTI-BULLYING CAMPAIGN MEDIA FOR CHILDREN AGED 9-12 YEARS OLD - Ainun Adila; Nurul Fitriana Bahri; Hanif Azhar (Gorga : Jurnal Seni Rupa, 2024)
Bullying cases in educational institutions have shown high numbers each year, with the highest cases in 2023 occurring in elementary schools. This was validated by the 4th-grade homeroom teacher at SDN 119 Cijagra, Mrs. Novriza Puspita Widiyana, S.Pd., who reported at least three bullying cases each month. Based on the characteristics of children aged 9-12, the use of educational toys can be an effective solution as a medium for campaigning anti-bullying values. Board games, which involve experimental learning, direct interaction, and actions that engage children's socio-emotional skills in relation to their environment, can effectively help children aged 9-12 absorb the values being taught through educational play tools. This study aims to design educational toys as a medium for anti-bullying campaigns that support the socio-emotional development of children aged 9-12 by applying the concept of board games. The research is conducted using a qualitative method with a case study approach and the ADDIE design method (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques used include observation, interviews, documentation, questionnaires, and literature review. This study is expected to serve as an effective and enjoyable campaign medium for children aged 9-12.